A processed human immunoglobulin epsilon gene has moved to chromosome 9. - Battey, J (1982)
Processed genes--genes that resemble processed RNA transcripts rather than interrupted genomic sequences--have been identified as dispersed members of several gene families. Here we describe a processed gene that is one of the three human IgE-like sequences present in the human genome. The processed IgE gene has precisely lost its three intervening sequences, thereby fusing its four coding domains. The homology of the gene to its functional counterpart ends in an adenine-rich tail followed by an 11-base-pair sequence that is directly repeated 150 base pairs 5' to its first coding domain. In addition, the processed gene is located on human chromosome 9 rather than on chromosome 14, the site of the active immunoglobulin locus. The structure and evident mobility of this sequence support the concept that sequences can move about in the genome via RNA intermediates and that processed genes are a prominent feature of genomic structure.